Methodological Issues of the RA Public Procurement Supervision - Nersisyan, Arshak (Bulletin of Yerevan University G: Economics, 2023)
The article presents the RA public procurement supervision methods. It refers to everything that is worth paying attention to during observing the procurement processes. The article also presents the definitions of monitoring and study of purchasing processes and their differences. Mechanisms of frequently repeated abuses in procurement processes are revealed, which are mainly carried out by circumventing one or another legislative requirement. There is an opinion that by monitoring procurement processes, many violations can be prevented without waiting for them to be committed. The article presents in sequence the stages of the purchase process and the episodes worthy of attention in those stages, focusing on which will be useful for persons exercising control powers. Some such mechanisms are also described, with the use of which the customers carry out abuses. In our opinion, it is necessary to detect and evaluate violations, first of all, taking into account their consequences and motivation. By this, we mean that offenses resulting from ignorance or inattention and intentional or negative intent should be classified. Violations considered procedural although occur more frequently in procurement processes, their importance should not be underestimated, because their presence makes the general picture of the purchasing process and the legality assessment more objective.
Keywords: public procurement; supervision; supervision mechanisms; contract execution; violations; abuses; monitoring; study; risk; legality assessment